2019
DOI: 10.1103/physrevlett.122.248003
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Property Relationships via Recovery Rheology in Viscoelastic Materials

Abstract: The recoverable strain is shown to correlate to the temporal evolution of microstructure via time-resolved small-angle neutron scattering (SANS) and dynamic shear rheology. Investigating two distinct polymeric materials of wormlike micelles and fibrin network, we demonstrate that, in addition to the nonlinear structure-property relationships, the shear and normal stress evolution is dictated by the recoverable strain. A distinct sequence of physical processes under large amplitude oscillatory shear (LAOS) is i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 85 publications
(119 reference statements)
6
39
0
Order By: Relevance
“…There has been recent experimental and theoretical interest in recoverable strain in polymers. Experiments by Lee et al have linked recoverable strain to microscopic structure and normal stress in two very different polymeric systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been recent experimental and theoretical interest in recoverable strain in polymers. Experiments by Lee et al have linked recoverable strain to microscopic structure and normal stress in two very different polymeric systems.…”
Section: Resultsmentioning
confidence: 99%
“…There has been recent experimental and theoretical interest in recoverable strain in polymers. Experiments by Lee et al have linked recoverable strain to microscopic structure and normal stress in two very different polymeric systems. In entangled polymers, the bulk of the strain is typically recovered in a very fast, time‐dependent, reversing shear flow, as the slow‐relaxing polymeric stress far exceeds the viscous stresses .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in searching for structure–property relationships, we have reported, via in situ rheo‐small‐angle neutron scattering (rheo‐SANS), a direct correlation between the macroscopic rheological response and structural evolution . It was demonstrated that under LAOS, the nonlinear viscoelastic properties, including the shear and normal stresses, shear modulus and viscosity, and the underlying segmental alignment, are all dictated by the recoverable strain , and not the total strain.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the way one perceives and analyzes particular responses may be influenced by concepts central to the prevailing theory in the field, and emerging experimental studies that challenge the theory have been reported . Motivated by recent advances in understanding out‐of‐equilibrium responses to LAOS via recoverable strain, the disagreement between the prevailing polymer dynamics theory and experiments, and experimental insights obtained from the recovery rheology, we aim to study the step strain response of a polymeric system with a complex shear history within the framework of recoverable strain. We concatenate two often‐performed tests, using an integer number of periods of LAOS to induce a complex nonlinear flow which is followed after some time by a single‐step strain.…”
Section: Introductionmentioning
confidence: 99%